The Difficulties of Online Learning as Encountered by Grade 12 HUMSS Students of Bestlink College of the Philippines: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Today, digital learning has become a necessary resource for students and schools worldwide. This is an entirely new way of education for many educational institutes that they have had to adopt. According to Hetrik (2020), online learning is “learning experiences in synchronous or asynchronous environments using different devices (e.g., mobile phones, laptops, etc.) with internet access. In these environments, students can be anywhere (independent) to learn and interact with instructors and other students. At the same time, it is easy to see both the benefits and relevance of online learning, such as flexibility, mobility, and affordability. Acknowledging the potential challenges with online learning for students was equally important. From the grade-schoolers, undergraduate and graduate students or e-learners at all age levels must overcome obstacles throughout online learning. This study aims to determine the difficulties Grade 12 HUMSS students encounter online learning and address the current situation or problems they face while pursuing their studies.  The researchers used qualitative and descriptive research methods as the research design. The instrument used to gather data was a survey questionnaire, while the convenience sampling method was used to select participants who would serve as the respondents. The study showed that most students encountered problems in online learning, such as difficulty in managing their time because of procrastination, which leads them to pass or do their activities late or are easily distracted by social media and online games. They also experience technical issues, specifically poor internet connection, lack of functioning digital devices and malfunction in Learning Management Systems (LMS). This study also revealed that regardless of the difficulties that students encountered, they could cope with them by doing their strategies and readily adopting the recommendations to improve and continue to pursue their studies through online learning.
Keywords: Online learning; online learning platform; Online learning tools